PERBANDINGAN PEMBERIAN PUPUK ORGANIK NADHIRA DAN PUPUK HYDROCOMPLEX TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascalonium L) - Darmadi Erwin Harahap; Adelina Fitriani Lubis (Yayasan Perguruan Kampus, 2023)
This study aims to determine the right dose of organic fertilizer (Nadhira) and hydrocomplex fertilizer on the growth and production of shallots (Allium ascalonium L). The experimental design used is non-factorial randomized group design (RAK), the treatment of Nadhira fertilizer consists of 3 levels, namely: N1 (1300 Kg/Ha or 5.2 grams/plant), N2 (1500 Kg/Ha or 6.0 grams/plant, N3 (1700 Kg/Ha or 6.8 grams/plant) and hydrocomplex fertilizer consists of 3 levels, namely: H1 (700 kg/Ha or 2.8 grams/plant), H2 (800 kg/Ha or 3.2 grams/plant), H3 (900 kg/Ha or 3.6 grams/plant). The results showed that the treatment of nadhira organic fertilizer and hydrocomplex fertilizer showed very significant differences in the average number of tillers (fruit) / plant, number of tubers / plant, wet weight of tubers / plant, and dry weight of tubers. From the fertilizer treatment, it can be compared that hydrocomplex fertilizer gives a better effect when compared to nadhira organic fertilizer on all parameters observed. The best nadhira organic fertilizer treatment was found in the N2 treatment, while the best hydrocomplex fertilizer treatment was found in the H2 treatment.